Role of lipid in the life cycles of ice-dependent and ice-independent populations of the copepod Paralabidocera antarctica - Kerrie Swadling; Nichols, PD; Gibson, JAE; Ritz, DA (2000)
We compared the lipid stores of coastal and lacustrine populations of the copepod Paralabidocera antarctica over a complete developmental cycle. The life cycle of the coastal population, which was reflected in their pattern of lipid storage, was coupled closely to the growth of sea ice. Nauplii entered the sea ice in early autumn and overwintered predominantly as the NIV stage, with triacylglycerol comprising up to 26 % of their dry weight (DW). During their rapid development from stages CI to CIV, much smaller quantities ( < 2 % DW) of triacylglycerol were present. The population underwent a habitat shift from the ice to the water column at the CIV stage, although adults remained close to the ice-water interface. Adults of both sexes initially contained high amounts of triacylglycerol as a proportion of their total lipid (50 % in males, 65 % in females), but these stores were depleted over the 3 wk-long period of mating and spawning. The lacustrine population of P. antarctica also accumulated triacylglycerol; however, their life cycle was largely independent of the ice cover on the lake. The CI to CIV stages of the lacustrine population contained more triacylglycerol than the same stages at the coastal site, suggesting that either they experienced short-term periods of starvation due to patchiness in the food supply or that their dietary intake was lipid-rich. Reproduction began 1 mo earlier in the lake population, and the lipid storage patterns of adults indicated a longer reproductive duration. The fatty acid composition of P. antarctica reflected that of particulate matter in the 2 environments, arguing for a relatively simple biochemical pathway in comparison to some of the larger pelagic copepods.